The determination and enhancement of compliant modes for actuation in structural assemblies - Bird,J; Santer,M; morrison,J (International Journal of Solids and Structures, 2016)
Linear algebra methods for determining modes of kinematic and static indeter-minacy in jointed frames are extended to reveal modes of compliance in oth-erwise rigid assemblies. These modes are extracted from a structural model,based on nite elements, via a singular value decomposition and yield the waysin which a structure can be most easily deformed. This modal approach alsoallows for the formulation of a reduced-order structural model, whereby relevantmodes are selected and used as the basis for the optimisation of a complaintstructure. The method detailed is shown to be a useful design tool, demon-strated by its application to a structure based on the Kagome lattice geometry.For certain frameworks, rst order e ects produce tightening under actuation.As a result, a scheme to adjust the modes to take nonlinear e ects into accountis also given.